Mechanism of Action of Lonicera caerulea Berry Polyphenols in Regulating Intestinal Microecology in Immunosuppressive Mice - ZHANG Lingyu, PAN Lijia, HOU Suxin, JIANG Shan, YANG Mei, CAO Jiazhen, XU Xiaohong, ZHANG Nan (Shipin Kexue, 2023)
Objective: In order to explore the effects of Lonicera caerulea berry polyphenols (LCBP) on immunity and intestinal flora in immunosuppressive mice. Methods: Thirty-two mice were randomly divided into a blank control group, a model group, a low-dose LCBP group and a high-dose LCBP group. Cyclophosphamide at 80 mg/(kg mb·d) was injected intraperitoneally after 17, 19 and 21 d of oral administration. Immune organ indices, routine blood biochemical indexes, intestinal microbial diversity and distribution, and the level of short chain fatty acids in colonic contents were investigated and colonic histopathology was examined by hematoxylin-eosin (HE) staining. Results: Compared with the model group, spleen and thymus indexes in the high-dose LCBP group significantly increased (P < 0.01). Also, the number of white blood cells, lymphocytes and platelets increased (P < 0.05), and so did the number of red blood cells and neutrophils (P < 0.01). LCBP increased the relative abundance of Firmicutes, Epsilonbacteraeota, Proteobacteria, Patescibacteria, Actinobacteria and Cyanobacteria in the intestinal tract of immunosuppressive mice and the concentrations of fecal short-chain fatty acids (SCFAs). Conclusion: LCBP can increase the type of intestinal flora, regulate the structural distribution of intestinal flora, alleviate intestinal injury and enhance immune function in immunosuppressive mice.